Membangun Content Delivery Network (CDN) menggunakan Reverse Proxy dan Caching berbasis Linux - Darujati, Cahyo; Al Azam, Moh Noor (Institut Teknologi Adhi Tama Surabaya, 2023)
Content Delivery Networks (CDN) improve website performance by distributing content closer to users. This paper explores the implementation of a self-hosted CDN using reverse proxy and caching technologies on a Linux-based infrastructure. Performance metrics such as response time, bandwidth usage, and server load are analyzed in two scenarios: with and without CDN. Our findings show a 50% reduction in response time and a 76% decrease in bandwidth consumption at the main server. The study highlights the benefits of localized caching and load balancing while discussing implementation challenges. This research provides a practical framework for organizations seeking cost-effective CDN solutions using open-source tools like Nginx and Varnish.